Strategic Approaches for Business Sustainability in a Volatile Global Economy - Pradwipa Mutianto (Arthatama: Journal of Business Management and Accounting, 2024)
In an era of persistent economic volatility, financial resilience is fundamental for business sustainability. This paper explores strategic approaches to enhancing financial resilience by integrating absorptive and adaptive capacities, financial literacy, and climate finance. Companies that develop robust financial structures, diversify revenue streams, and adopt effective risk management strategies are better positioned to navigate global uncertainties. Moreover, financial literacy enhances decision-making capabilities, fostering adaptive financial strategies that support long-term stability. The paper also highlights the growing relevance of climate finance in ensuring sustainability, particularly for businesses in developing economies. The interplay between geopolitical risks, economic fluctuations, and financial strategies underscores the necessity of dynamic financial planning. By examining existing literature and strategic frameworks, this study provides actionable insights for businesses seeking to fortify their financial resilience in an increasingly uncertain global landscape. The findings suggest that organizations must adopt a proactive approach, leveraging financial innovation, regulatory frameworks, and sustainability-focused investments to remain competitive.